Potensi Reduksi Sampah Melalui Pengelolaan Sampah Perkotaan Di Tps Kecamatan Mataram - Rahmaniah, Rasyidatur; Meidiana, Christia; Dwi Ari, Ismu Rini (Fakultas Teknik, Universitas Brawijaya, 2013)
The increasing of service in waste management without any effort in reducing the waste can cause the increasing volume of waste. Thus, we need waste processing activity close to waste source, such as in transfer point. The use of high-effectively tools and infrastructures are able to increase the performance of waste processing. There is increase of waste management performance which needs to be balance with economic-valued waste management activity. This research aims to recognize the right recommendation for waste management at transfer point in Subdistrict of Mataram related to its potential waste reduction by identify operational performance, factors effecting the waste processing, and knowing of potential of waste reduction in transfer point in Subdistrict of Mataram. The research methodology used are analysis of operational performance in waste processing, analysis of binary logistic regression, dan analysis of mass balance. Result shows of 18 transfer points are 6 transfer point classified to have appropriate performance and 12 transfer point classifeid to have not appropriate performance. Factors effecting the waste processing in Subdistrict of Mataram are waste colecting tools, frequency of waste collecting, waste collecting pattern, frequency of waste transfer, waste transportation tools, frequency of waste transport, and waste transport pattern. If waste processing activity, potential of waste reduction are 5%. There is potential of waste reduction which can reduce amount of waste tramsfered to TPA.Keywords: Transfer point, Municipal Solid Waste Management,Waste Reduction.